1980
DOI: 10.1002/pol.1980.170180713
|View full text |Cite
|
Sign up to set email alerts
|

Model simulation studies of complex free radical reactions: The graft copolymerization of styrene and acrylonitrile onto ethylene‐propylene‐isopropylidendicyclopentadiene terpolymer

Abstract: A kinetic analysis without steady approximation of the graft copolymerization of styrene‐acrylonitrile onto ethylene‐ propylene‐isopropylidendicyclopentadiene terpolymer (EP‐IPDCP) is described. Some of the kinetic constants were experimentally determined. The grafting process is interpreted mainly in terms of the attack on EP‐IPDCP by benzoyloxy radicals; phenyl radicals play a minor negative role by enhancing the rate of homopolymerization. A major contribution to the grafting yield is made by the propagatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This result can be explained as follows: the viscosity of the reaction mass increases as EPDM content increases and, as a result, the diffusion of monomer into EPDM molecules becomes difficult and the monomer tends to copolymerization. According to Faucitano,9 the mechanism of the grafting process, of styrene–acrylonitrile onto EPDM, was that the benzoyloxy radicals attack EPDM first and then induce the graft polymerization of monomers. Consequently it can be concluded that, when a higher concentration of EPDM is charged, a higher ratio of formation rate of EPDM macromolecules radicals to monomer radicals results and then will cause a higher grafting efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be explained as follows: the viscosity of the reaction mass increases as EPDM content increases and, as a result, the diffusion of monomer into EPDM molecules becomes difficult and the monomer tends to copolymerization. According to Faucitano,9 the mechanism of the grafting process, of styrene–acrylonitrile onto EPDM, was that the benzoyloxy radicals attack EPDM first and then induce the graft polymerization of monomers. Consequently it can be concluded that, when a higher concentration of EPDM is charged, a higher ratio of formation rate of EPDM macromolecules radicals to monomer radicals results and then will cause a higher grafting efficiency.…”
Section: Resultsmentioning
confidence: 99%